Rhetorical terms in Safavid biographies - محمد رضایی; آرزو نقی زاده (مطالعات زبانی و بلاغی)
Rhetoric and eloquence are among literary sciences âwhich help the critics in reviewing texts. Rhetoricians have âspecial rules for words and speakers which may change âduring the period of literary history along with the changing âtaste of scholars and critics . A literary text as having the âcharacteristics of the rhetoric and eloquence may be reviewed âat any period of history in a different way. In the Safavid era âwith the fusion of Persian poetry and the taste of Hindi poets ââ,further developments of this sort happened. In that era the âbiographers by changing the standards of Rhetoric and âeloquence have used some terms. Studying these terms helps âto understand their perspectives towards rhetoric and eloquent âtexts.â